2012
DOI: 10.1183/09031936.00030612
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis treatment outcome monitoring in European Union countries: systematic review

Abstract: Treatment success measured by treatment outcome monitoring (TOM) is a key programmatic output of tuberculosis (TB) control programmes. We performed a systematic literature review on national-level TOM in the 30 European Union (EU)/European Economic Areas (EEA) countries to summarise methods used to collect and report data on TOM.Online reference bibliographic databases PubMed/MEDLINE and EMBASE were searched to identify relevant indexed and non-indexed literature published between January 2000 and August 2010.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
4
19
0
Order By: Relevance
“…Systematic reviews have highlighted that there are limited large-scale data on TB treatment outcomes. Another systematic review of national-level TB treatment outcomes among the 30 European Union /European Economic Area countries indicated the same [9]. The WHO Global TB Report provide such data at national level; however detailed analysis of individual patient data, as well as associations between unfavorable treatment outcomes and selected demographic and clinical characteristics, are not reported [5].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews have highlighted that there are limited large-scale data on TB treatment outcomes. Another systematic review of national-level TB treatment outcomes among the 30 European Union /European Economic Area countries indicated the same [9]. The WHO Global TB Report provide such data at national level; however detailed analysis of individual patient data, as well as associations between unfavorable treatment outcomes and selected demographic and clinical characteristics, are not reported [5].…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses have shown that if patients fail to achieve sputum culture conversion (SCC) from growth of MTB to no growth of MTB early in the course of MDR-TB treatment, they have a much higher likelihood of a poor outcome at the end of treatment, including death [8, 9]. Even in high resource settings such as the European Union (EU), surveillance data showed that treatment success averaged from 30–49% for 2007–2008 MDR-TB cohorts [10, 11], although under reporting of treatment outcomes may have affected these results [12]. …”
mentioning
confidence: 99%
“…Infectious disease surveillance is an import tool in detecting unusual events, assessing trends and monitoring the impact of programmes [15][16][17][18][19][20][21][22][23]. Legionnaires' disease is notifiable in all 27 European Union countries, plus Iceland and Norway.…”
mentioning
confidence: 99%